Kepastian Hukum Terhadap Standar Pelayanan Publik Dalam Pelayanan Izin Usaha : Studi di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Pematang Siantar - Rudy Rudy; Budiman Ginting; Sunarmi Sunarmi; Edy Ikhsan (USU LAW JOURNAL, 2019)
Abstract. Implementation of Mayor Regulation No. 8 of 2017 concerning Delegation of Authority Signing of Licensing to the Head of Pematangsiantar City One Stop Service and Integrated Investment Services that reflects disturbed justice and public services based on the principles of good government law which tend to be a manifestation of justice and benefit is not carried out optimally.   Keywords: public services, business permit services, and pematangsiantar city